2020
DOI: 10.20944/preprints202006.0302.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Matters: Climate Change, Gender Bias, and Women's Farming in the Global South and North

Abstract: Can investing in women’s agriculture increase productivity? This paper argues that it can. We assess climate impacts and gender bias on women’s production in the global South and North and challenge the male model of agricultural development to argue further that women’s farming approaches can be more sustainable. Level-based analysis (global, regional, local) draws on literature review, including authors’ published longitudinal field research in Ghana and the United Sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Each of these indicators takes gridded heat data and overlays them with relevant exposure and The health impacts of climate change are both underpinned and amplified by gender norms and gender inequities, with numerous examples cited throughout this report. 29 Gender also influences who sets the agenda and drives responses to climate change. Evidence shows that greater representation of women in parliament is associated with stronger climate change policies.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitymentioning
confidence: 99%
“…Each of these indicators takes gridded heat data and overlays them with relevant exposure and The health impacts of climate change are both underpinned and amplified by gender norms and gender inequities, with numerous examples cited throughout this report. 29 Gender also influences who sets the agenda and drives responses to climate change. Evidence shows that greater representation of women in parliament is associated with stronger climate change policies.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitymentioning
confidence: 99%
“…• Gender inequalities. Women play the central role in in situ agrobiodiversity conservation and development (Glazebrook et al, 2020). Seed exchange networks empower women.…”
Section: Inequalities and Climate Changementioning
confidence: 99%
“…This implies that access to land is gendered with more male cassava farmers having paralleled unequalled easy access to land for agriculture. Glazebrook et al (2020), indicated gender disparity in access to land in the global south and north.…”
Section: Relationship Between Gender Access To Land and Creditmentioning
confidence: 99%
“…Women's participation in agricultural production significantly contributes to the global food security (Glazebrook et al, 2020). Their commitment to the agricultural work force is additionally higher than men's (Anderson et al, 2021;Glazebrook et al, 2020).…”
Section: Introductionmentioning
confidence: 99%